Does omega‐3 supplementation reduce cardiac mortality?. Issue 1 (January 2018) - Harris, Lisa; Swinson, Karl
Abstract : EVIDENCE‐BASED ANSWER : No. Omega‐3 fatty acid supplementation does not reduce cardiac mortality in primary or secondary prevention (SOR: A, meta‐analysis of RCTs and 2 RCTs).